2015
DOI: 10.1128/aem.02856-14
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chitosan Microparticles for Reduction of Vibrio Species in Seawater and Live Oysters (Crassostrea virginica)

Abstract: bHuman Vibrio infections associated with consumption of raw shellfish greatly impact the seafood industry. Vibrio cholerae-related disease is occasionally attributed to seafood, but V. vulnificus and V. parahaemolyticus are the primary targets of postharvest processing (PHP) efforts in the United States, as they pose the greatest threat to the industry. Most successful PHP treatments for Vibrio reduction also kill the molluscs and are not suitable for the lucrative half-shell market, while nonlethal practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Prior reports also found CM activity was similarly temperature‐ (Fang et al . ) and pH‐dependent (Jeon et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior reports also found CM activity was similarly temperature‐ (Fang et al . ) and pH‐dependent (Jeon et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CM treatment significantly decreased or eliminated survival of Vibrio species in seawater (pH 7·4), as well as in live oysters (Fang et al . ). CM reduced shedding of pathogenic Escherichia coli O157:H7 for infected cattle (Jeong et al .…”
Section: Introductionmentioning
confidence: 97%
“…Fang et al . () evaluated anti‐vibrio activity of 0.5% w/v chitosan microparticles (prepared in AC) against V. cholerae, V. vulnificus and V. parahaemolyticus in broth cultures. They reported growth cessation of V. cholerae , V. vulnificus and V. parahaemolyticus , reducing culturable levels to a non‐detectable level (<10 CFU mL −1 ) after 3 h post‐treatment.…”
Section: Vibrio Cholerae Vibrio Vulnificus and Vibrio Parahaemolyticusmentioning
confidence: 99%
“…For instance, Jung et al (2010) reported that 0.05% acid (AC)-soluble chitosan with 99% DD completely inhibited V. vulnificus and V. parahaemolyticus after 24 h at 37°C. Fang et al (2015) evaluated anti-vibrio activity of 0.5% w/v chitosan microparticles (prepared in AC) against V. cholerae, V. vulnificus and V. parahaemolyticus in broth cultures. They reported growth cessation of V. cholerae, V. vulnificus and V. parahaemolyticus, reducing culturable levels to a non-detectable level (<10 CFU mL À1 ) after 3 h post-treatment.…”
Section: Salmonella Typhimuriummentioning
confidence: 99%
“…CN/CM were reported to be effective food preservatives (Fang et al . ; Pilon et al . ; Chouljenko et al .…”
Section: Preparation Of Chitosanmentioning
confidence: 99%